Aging Brain: Prevention of Oxidative Stress by Vitamin E and Exercise - Sambe Asha Devi (The Scientific World Journal)
With aging, the brain undergoes neuronal loss in many areas. Although the loss of cells in the cerebral cortex, in particular the frontal cortex, has been recognized with aging, the influence of synaptic losses has a larger impact on cognitive decline. Much of the recent research on animals, as well as humans, has been aimed at slowing the cognitive decline through enrichment, and it has been found that the key factors are antioxidants and exercise. Several reports support the concept that regular supplementation of vitamin E and physical activity from as early as middle age can slow the cognitive decline observed during the later years. A few studies have also suggested that exercise is analogous to acetylcholine esterase inhibitors that are also used extensively to treat cognitive impairment and dementia in Alzheimer's disease. In addition, reports also support that vitamin E and exercise may act synergistically to overcome free radical injury and oxidative stress in the aging brain.